Physiological role of β-carotene monohydroxylase (CYP97H1) in carotenoid biosynthesis in Euglena gracilis. (January 2019) - Tamaki, Shun; Kato, Shota; Shinomura, Tomoko; Ishikawa, Takahiro; Imaishi, Hiromasa
Graphical abstract: Highlights: We identified the β-carotene monohydroxylase gene ( EgCYP97H1 ) in Euglena gracilis . This study is the first evidence of β-carotene monohydroxylase. EgCYP97H1 was essential for carotenoid biosynthesis and normal growth in this alga. Abstract: Some carotenoids are found in the Euglena gracilis, including β-carotene, diadinoxanthin, diatoxanthins, and neoxanthin as the major species; however, the molecular mechanism underlying carotenoid biosynthesis in E. gracilis is not well understood. To clarify the pathway and regulation of carotenoid biosynthesis in this alga, we functionally characterized the cytochrome P450 (CYP)-type carotene hydroxylase gene EgCYP97H1 . Heterologous in vivo enzyme assay in E. coli indicated that EgCYP97H1 hydroxylated β-carotene to β-cryptoxanthin. E. gracilis cells suppressing EgCYP97H1 resulted in marked growth inhibition and reductions in total carotenoid and chlorophyll contents. Analysis of carotenoid composition revealed that suppression of EgCYP97H1 resulted in higher level of β-carotene, suggesting that EgCYP97H1 is physiologically essential for carotenoid biosynthesis and thus normal cell growth. To our knowledge, this is the first time EgCYP97H1 has been suggested to be β-carotene monohydroxylase, but not β-carotene dihydroxylase. Moreover, during light adaptation of dark-grown E. gracilis, transcript levels of the carotenoid biosynthetic genes ( EgCYP97H1, geranylgeranyl pyrophosphate synthase EgcrtE, and phytoene synthase EgcrtB ) remained virtually unchanged. In contrast, carotenoid accumulation in E . gracilis grown under the same conditions was inhibited by treatment with a translational inhibitor but not a transcriptional inhibitor, indicating that photo-responsive carotenoid biosynthesis is regulated post-transcriptionally in this alga.